2004
DOI: 10.1159/000080993
|View full text |Cite
|
Sign up to set email alerts
|

Combined Irinotecan and Oxaliplatin in Patients with Advanced Pre-Treated Pancreatic Cancer

Abstract: Objectives: This study evaluated the clinical activity and toxicity of combination chemotherapy with irinotecan and oxaliplatin in patients with advanced pancreatic cancer that had progressed despite ≧1 course of a gemcitabine-containing regimen. Methods: Thirty patients with metastatic pancreatic cancer and Karnofsky performance status ≧70 received oxaliplatin 60 mg/m2 on days 1 + 15 and irinotecan 60 mg/m2 on days 1 + 8 + 15 every 4 weeks. Patients were assessed on the basis of clinical… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
29
0

Year Published

2006
2006
2017
2017

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 75 publications
(34 citation statements)
references
References 17 publications
5
29
0
Order By: Relevance
“…The present study reports the findings on a single center cohort of patients who received second-line gemcitabine treatment for advanced-stage pancreatic adenocarcinoma. A survival of 3.6 months with second-line chemotherapy was observed, which is in agreement with previous published data (Table I) (7)(8)(9)(10)14,15,(22)(23)(24)(25)(26)(27)(28)(29)(30)(31). Response to gemcitabine therapy at the first follow-up evaluation (at 2 months) impacted significantly the OS of the patients.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…The present study reports the findings on a single center cohort of patients who received second-line gemcitabine treatment for advanced-stage pancreatic adenocarcinoma. A survival of 3.6 months with second-line chemotherapy was observed, which is in agreement with previous published data (Table I) (7)(8)(9)(10)14,15,(22)(23)(24)(25)(26)(27)(28)(29)(30)(31). Response to gemcitabine therapy at the first follow-up evaluation (at 2 months) impacted significantly the OS of the patients.…”
Section: Discussionsupporting
confidence: 92%
“…Indeed, based on promising results from phase II studies (8)(9)(10), a randomized-phase III study demonstrated that the median survival time upon failure of first-line gemcitabine treatment increased to 21 weeks with oxaliplatin/folinic acid/5-fluorouracil treatment and best supportive care (BSC) compared with only 10 weeks in patients receiving BSC alone (7). Other studies have reported different experiences with second-line treatments subsequent to gemcitabine, with modest efficacy for patients who still have a good ECOG performance status (Table I).…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, antagonism with AdDD was not observed in any cell line, suggesting that the deletion of E1B19K might push the balance towards cell death. The degree of sensitization with the combination of AdDD and irinotecan, a topoisomerase I inhibitor, 34,44 was similar to that obtained in combination with gemcitabine in SUIT-2, PT45 and MIA PaCa-2 cells, with two-to fourfold reductions in EC 50 values. In contrast to gemcitabine, the enhancement of cell killing was independent of the sensitivity of each cell line to drug and might reflect the different mechanisms of action for these drugs.…”
Section: Discussionsupporting
confidence: 59%
“…Irinotecan has been tested both as single agent and in combination with oxaliplatin or fluoropyrimidines showing some activity and an acceptable toxicity profile (Yi et al, 2009;Cantore et al, 2004). A direct comparison between oxaliplatin-and irinotecan-based regimens was made by Hwang and colleagues in a small randomized phase II trial (Hwang et al, 2009).…”
Section: Gemcitabine-resistant Diseasementioning
confidence: 99%